Market-Driven Capabilities dan Competitive Advantage pada UMKM Pangan Lokal Kabupaten Jombang: Peran Inovasi dan Adopsi Teknologi Digital - Rahayu Rahayu (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to examine the effects of Market Sensing Capability, Customer Insight Capability, and Digital Marketing Capability on Competitive Advantage through the mediating role of Innovation Capability and the moderating role of Digital Technology Adoption among local food SMEs in Jombang Regency, Indonesia. A quantitative approach with an explanatory research design was employed. Data were collected through a survey of 200 owners and managers of local food SMEs selected using purposive sampling. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings reveal that Market Sensing Capability, Customer Insight Capability, and Digital Marketing Capability have positive and significant effects on Innovation Capability. Furthermore, Innovation Capability has a positive and significant effect on Competitive Advantage. In terms of direct effects, Customer Insight Capability significantly enhances Competitive Advantage, whereas Market Sensing Capability and Digital Marketing Capability do not show significant direct effects. The mediation analysis demonstrates that Innovation Capability significantly mediates the relationships between the three market-based capabilities and Competitive Advantage. However, Digital Technology Adoption does not significantly moderate the relationship between Innovation Capability and Competitive Advantage. These findings suggest that the competitive advantage of local food SMEs is driven more by their ability to understand customer needs and generate innovation than by market sensing or digital marketing activities alone. This study also provides practical implications by emphasizing that strengthening innovation capability and customer understanding should become strategic priorities for local food SMEs in achieving sustainable competitive advantage in an increasingly dynamic digital business environment.